EMPLOYER REQUIREMENTS FOR THE COMPETENCE OF TEACHERS – YOUNG SPECIALISTS (Education in the 21st Century, 2023)
Today, when higher education becomes more and more practice-oriented, the importance of considering the opinions of all those interested in training specialists for the school is growing. These are the direct employers - the heads of educational institutions where the graduates of the pedagogical university go to work.In order to increase the competitiveness of BSPU graduates, surveys of employers were conducted, which made it possible to identify what competencies need to be formed in students at the stage of university education, which should be given special attention when organizing the educational process, etc.The article provides original data from a survey of employers on the formation and demand for key competencies among graduates of a pedagogical university, their importance for professional success. Information on the satisfaction of employers with the quality of theoretical and methodological training of future teachers is given, recommendations are given on attracting employers to participate in improving the educational process.
Keywords: Employers, graduates of pedagogical specialties, key competencies, teachers, young specialists, the demand for competencies, the formation of competencies, a deficit of competencies